2020
DOI: 10.1101/2020.12.09.417162
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deletion of the Clock GenePeriod2 (Per2)in Glial Cells Alters Mood-Related Behavior in Mice

Abstract: The circadian clock regulates many biochemical and physiological pathways, and lack of clock genes, such as Period (Per) 2, do not only affect circadian activity rhythms, but can also modulate food-anticipatory and mood-related behaviors. However, it is not known how cell-type specific expression of Per2 contributes to these behaviors. In this study, we find that Per2 in glial cells is important for balancing mood-related behaviors. Genetic and adeno-associated virus-mediated deletion of Per2 in glial cells of… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…However, neuronal Per2 knockout also reduces despair, but not anxiety responses. Astrocytic Bmal1 deletion in the NAc did not affect despair or anxiety (Martini et al, 2021). A recent study demonstrated that astrocytes in the NAc showed strong molecular rhythms which regulates NAc metabolic homeostasis and behavior.…”
Section: Ventral Tegmental Area and Nucleus Accumbensmentioning
confidence: 93%
See 1 more Smart Citation
“…However, neuronal Per2 knockout also reduces despair, but not anxiety responses. Astrocytic Bmal1 deletion in the NAc did not affect despair or anxiety (Martini et al, 2021). A recent study demonstrated that astrocytes in the NAc showed strong molecular rhythms which regulates NAc metabolic homeostasis and behavior.…”
Section: Ventral Tegmental Area and Nucleus Accumbensmentioning
confidence: 93%
“…Importantly, astrocytes also contain a circadian molecular clock and clock genes regulate astrocyte functions (Prolo et al, 2005;Brancaccio et al, 2017). Deletion of Per2 in mouse astrocytes reduced despair and anxiety associated with increased GABA transporter 2 and dopamine receptor D3 mRNA and reduced glutamate levels in the NAc (Martini et al, 2021). However, neuronal Per2 knockout also reduces despair, but not anxiety responses.…”
Section: Ventral Tegmental Area and Nucleus Accumbensmentioning
confidence: 99%